2010
DOI: 10.47102/annals-acadmedsg.v39n9p686
|View full text |Cite
|
Sign up to set email alerts
|

The Pedagogical Value of a Student-run Community-based Experiential Learning Project: The Yong Loo Lin School of Medicine Public Health Screening

Abstract: Introduction: We assessed the pedagogical value of a student-led community-based experiential learning project called the Public Health Screening (PHS) run by medical and nursing students of the National University of Singapore’s Yong Loo Lin School of Medicine (NUS YLLSoM). Materials and Methods: We conducted a cross-sectional study using a self-administered anonymised questionnaire on medical and nursing students who participated in PHS using the Fund for the Improvement of Postsecondary Education (FIPSE) Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The third most frequently reported learning outcome associated with SRC participation revolved around empathy/compassion for underserved individuals (n = 34), 15 , 18 , 25 , 27–29 , 42 , 53 , 55 , 57 , 59 , 62 , 75 , 83–87 in particular improving attitudes towards, 15 , 18 , 25 , 28 , 34 , 88 as well as awareness and understanding and of the needs and social reality of, the underserved. 19 , 22 , 29 , 31 , 35 , 36 , 55 , 57 , 59 , 60 , 62 , 66 , 68 , 70 , 75 , 76 , 82 , 84 , 86 , 89–92 Though one study reported no change in overall attitudes towards homeless patients. 93 Finally, improved skills working with indigenous populations were noted as a learning outcome in one study.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The third most frequently reported learning outcome associated with SRC participation revolved around empathy/compassion for underserved individuals (n = 34), 15 , 18 , 25 , 27–29 , 42 , 53 , 55 , 57 , 59 , 62 , 75 , 83–87 in particular improving attitudes towards, 15 , 18 , 25 , 28 , 34 , 88 as well as awareness and understanding and of the needs and social reality of, the underserved. 19 , 22 , 29 , 31 , 35 , 36 , 55 , 57 , 59 , 60 , 62 , 66 , 68 , 70 , 75 , 76 , 82 , 84 , 86 , 89–92 Though one study reported no change in overall attitudes towards homeless patients. 93 Finally, improved skills working with indigenous populations were noted as a learning outcome in one study.…”
Section: Resultsmentioning
confidence: 98%
“… Simmons et al (2019) 73 Survey Simon et al (2019) 82 Survey X Stephens et al (2015) 36 Survey ? X Vaikunth et al (2014) 98 Academic record review Wee et al (2010) 60 Survey ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations